KEDUDUKAN SENTANA RAJEG DALAM SISTEM PEWARISAN ADAT BALI DI BANJAR SE KEBONKURI DESA KESIMAN KECAMATAN DENPASAR TIMUR KOTA DENPASAR BALI - , PUTU ABDI PUTRA SARJANA, SH; , Dr. Sulastriyono, S.H.,M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research examines the position of Sentana Rajeg in the inheritance system of Balinese Custom in Banjar se Kebonkuri Kesiman village East Denpasar Subdistrict Denpasar Bali City. This research aims to find out and analyze the emerging background of nyentana/nyeburin in Kesiman village East Denpasar Subdistrict Denpasar Bali City and how the position of Sentana Rajeg in the inheritance system of Balinese Custom in Banjar se Kebonkuri Kesiman village East Denpasar Subdistrict Denpasar Bali City. This is an empirical judicial research that is research that based on field study. This research employ library research by using document study that learn and analyze the law material documents related to the research problems and field study that is by interviewing with the imformant and respondents. The factors causing nyentana/nyeburin marriage is to avoid camput right, because do not have brothers, parentsâ desire, as the only daughter, and the other supporting factors because the parents want to give the entire legacy to their real child. The position of sentana rajeg in the inheritance system of Balinese Custom is that the daughter placed as the inheritee similar with the son as an inheritee. Nevertheless, the daughter just has the heritage of her parentsâ properties. Whereas the duty to represent the family as a banjar member, member of custom village, and to maintain the pura (pemerajaan) are being inherited to the husband who carry out the nyeburin marriage.